COVID-19, Coronavirus, Wuhan Virus, or China Virus? Understanding How to “Do No Harm” When Naming an Infectious Disease - Masters-Waage, Theodore C.; Jha, Nilotpal; Reb, Jochen (Frontiers in Psychology, 2020)
When labelling an infectious disease, officially sanctioned scientific names, e.g. “H1N1 virus”, are recommended over place-specific names, e.g. “Spanish flu”. This is due to concerns from policymakers and the WHO that the latter might lead to unintended stigmatization. However, with little empirical support for such negative consequences, authorities might be focusing limited resources on an overstated issue. This paper empirically investigates the impact of naming against the current backdrop of the 2019-20 pandemic. The first hypothesis posited that using place-specific names associated with China (e.g. Wuhan Virus or China Virus) leads to greater levels of sinophobia, the negative stigmatization of Chinese individuals. The second hypothesis posited that using a scientific name (e.g. Coronavirus or COVID-19) leads to increased anxiety, risk aversion, beliefs about the contagiousness of the virus, and beliefs about mortality rate. Results from two preregistered studies (N(Study 1) = 504; N(Study 2) = 412), conducted across three countries with the first study during the early outbreak (April 2020) and the second study at a later stage of the pandemic (August 2020), found no evidence of any adverse effects of naming on sinophobia and strong support for the null hypothesis using Bayesian analyses. Moreover, analyses found no impact of naming on anxiety, risk aversion, beliefs about the contagiousness of the virus, or beliefs about mortality rate, with mild to strong support for the null hypothesis across outcomes. Exploratory analyses also found no evidence for the effect of naming being moderated by political affiliation. In conclusion, results provide no evidence that virus naming impacted individual’s attitudes towards Chinese individuals or perceptions of the virus, with the majority of analyses finding strong support for the null hypothesis. Therefore, based on the current evidence, it appears that the importance given to naming infectious diseases might be inflated.